Honeybee Venom Synergistically Enhances the Cytotoxic Effect of CNS Drugs in HT-29 Colon and MCF-7 Breast Cancer Cell Lines - Diana Duarte; Soraia I. Falcão; Iouraouine El Mehdi; Miguel Vilas-Boas; Nuno Vale (MDPI AG, 2022)
5-fluorouracil (5-FU) and doxorubicin (DOX) are potent anti-tumour agents commonly used for colon and breast cancer therapy, respectively. However, their clinical application is limited by their side effects and the development of drug resistance. Honeybee venom is a complex mixture of substances that has been reported to be effective against different cancer cells. Its active compound is melittin, a positively charged amphipathic peptide that interacts with the phospholipids of the cell membrane, forming pores that enable the internalization of small molecules with cytotoxic activities,. and consequently, causing cell death. Some central nervous system (CNS) drugs have recently demonstrated great anti-cancer potential, both in vitro, in vivo and in clinical trials, being promising candidates for drug repurposing in oncology. The present work evaluated the anti-cancer efficacy of honeybee venom in combination with chemotherapeutic or CNS drugs in HT-29 colon and MCF-7 breast cancer cell lines. The chemical characterization of a Portuguese sample of honeybee venom was done by LC-DAD-ESI/MSn analysis. For single treatments, cells were incubated with increasing concentrations of bee venom. For combination treatments, increasing concentrations of bee venom were first combined with the half-maximal inhibitory concentration (IC50) of 5-FU and DOX, in HT-29 and MCF-7 cells, respectively. Cells were also treated with increasing concentrations of bee venom in combination with the IC50 value of four CNS drugs (fluphenazine, fluoxetine, sertraline and thioridazine). Cytotoxicity was evaluated by MTT and SRB assays. The combination index (CI) value was calculated using CompuSyn software, based on the Chou-Talalay method. Synergy scores of different reference models (HSA, Loewe, ZIP and Bliss) were also calculated using SynergyFinder. The results demonstrate that honeybee venom is active against HT-29 colon and MCF-7 breast cancer cells, having better anti-tumour activity in MCF-7 cells. It was found that bee venom combined with 5-FU and fluphenazine in HT-29 cells resulted in less cytotoxic effects compared to the co-treatment of fluoxetine, sertraline and thioridazine plus bee venom, which resulted in less than 15% of viable cells for the whole range of concentrations. The combination of MCF-7 cells with repurposed drugs plus honeybee venom resulted in better anti-cancer efficacies than with DOX, notably for lower concentrations. A combination of fluoxetine and thioridazine plus honeybee venom resulted in less than 40% of viable cells for all ranges of concentrations. These results support that the combination of honeybee venom with repurposed drugs and chemotherapeutic agents can help improve their anti-cancer activity, especially for lower concentrations, in both cell lines. Overall, the present study corroborates the enormous bioactive potential of honeybee venom for colon and breast cancer treatments, both alone and in combination with chemotherapy or repurposed drugs.